Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Numbered Heads Together Terhadap Pemahaman Konsep Matematika Peserta Didik Kelas VIII SMP Negeri 25 Padang - YUNI SAFITRI (Jurnal Edukasi dan Penelitian Matematika, 2020)
his study aims to determine the understanding of mathematical concepts of students who learn with cooperative learning models of the NHT type is better than understanding the mathematical concepts of students who learn by direct learning in class VIII SMP Negeri 25 Padang. This type of research is a quasi-experimental design with Static Group Design. The research sample is class VIII.3 as the experimental class and class VIII.2 as the control class. The instrument used was the final test of concept understanding in the form of essay questions. Data analysis used t-test. Based on the analysis of the final test results of understanding students' mathematical concepts, p-value is obtained = 0.019, because p-value <0.05 then H0 is rejected. This shows that the ability to understand mathematical concepts of students who learn with cooperative learning models of the NHT type is better than the ability to understand mathematical concepts of students who learn by direct learning.Keywords : Understanding Mathematical Concepts, Numbered Heads Together, Direct Learning..